Las fuentes del historiador económico (y el investigador en general) y los medios digitales - Pérez De Perceval Verde, Miguel (EDITUM. Ediciones de la Universidad de Murcia, 2025)
This book deepens the techniques of digitalization of documents, their computer treatment and the exploitation of such information. First, the need to work with digitized sources is raised, many of which we need to process them personally.Below are the materials (photographic machines and corresponding equipment) more appropriate for this work and the procedures to get adequate copies and save time.Once the material is achieved (own or provided by the files) some retouching systems and programs are described and, especially, of information storage. The means that is advised is that of PDF file, of which its usefulness and its use are highlighted as a tool for exploitation of the sources (markers, comments, ocr ...) and exchange of our research work.